Dual‐Targeting Heparin‐Based Nanoparticles that Re‐Assemble in Blood for Glioma Therapy through Both Anti‐Proliferation and Anti‐Angiogenesis. (22nd September 2016) - Wang, Jihui; Yang, Yuantao; Zhang, Yonghong; Huang, Min; Zhou, Zhenjun; Luo, Wanxian; Tang, Jiao; Wang, Jianguo; Xiao, Qian; Chen, Huajian; Cai, Yingqian; Sun, Xinlin; et al.
Abstract : The efficient and specific delivery of nanoparticles (NPs) to brain tumors is crucial for successful glioma treatment. Heparin‐based polymers decorated with two peptides self‐assemble into multi‐functional NPs that specifically target glioma cells. These NPs re‐self‐assemble to a smaller size in blood, which is beneficial for in‐vivo brain drug delivery. The hydrodynamic size of one type of these NPs is 63 ± 11 nm under blood‐mimic conditions (10% fetal bovine serum), but it is 164 ± 16 nm in water. Additionally their zeta potential is more neutral in the blood‐mimic conditions. Transmission electron microscopy reveals the morphology of the spherical NPs. In vitro experiments demonstrate that the NPs exhibit a high cellular uptake and the ability to efficiently discourage proliferation, endothelial‐lined vessels, and vasculogenic mimicry. In vivo studies demonstrate that the NPs can by‐pass the normal blood–brain and blood–(brain tumor) barriers and specifically accumulate in glioma tissues; moreover, they present an excellent anti‐glioma effect in subcutaneous/intracranial glioma‐bearing mice. Their superiority is due to their appropriate size in blood and the synergic effect arising from their targeting of two different receptors. The data suggests that these NPs are ideal for anti‐glioma therapy. Abstract : Nanoparticle (NP) formation by the aqueous self‐assembly of a heparin‐based polymer containing two targeting peptides is reported . The peptides target different cell receptors, and their structures enable the NPs to rearrange and re‐selfassemble in blood. Their dual‐targeting capability and resulting size in blood make them suitable for in vivo brain drug delivery. By‐passing the vascular–tumor barrier and accumulating specifically in glioma, these NPs exhibit an excellent anti‐glioma effect in mice.